TRANSLATION OF SHORTENED WORDS IN THE TERMINOLOGY OF SURGERY - Elmurod Umrzoqovich, Tursunov (International Journal of Business, Law, and Education, 2021)
The aim of article is to discuss and illustrate special features of translating surgery terms and their interpretation. Following the aspect, it covers common features on the special translation comprising: abbreviations, acronyms, shortened words and their types within the terms of surgery. Therefore it is crucial issue for translators to have ample knowledge and idea on surgery; medical background information and acquainting with special acronyms in international medical filed. The paper constitutes supported examples as well as samples on the provided theme. The readers can get enough data and opinion on the topic by means of article through provided points